Ghats at the southern end of Banganga Tank - Ghosh, Ayan (2023)
Hindu pilgrims perform parikrama along a path going around Banganga Tank, starting from the south end. The important temples are located on the parikrama path. The ghats have spatial division according to specific rituals; south and west are used for rituals of the dead, and north and east are used for auspicious rites.